Untersuchungen zur Anlagen- und Prozeßdiagnostik für das Schneiden mit CO2-Hochleistungslasern - Biermann, Stephan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1991)
In this work the main measurable variables of machine and process diagnostics for high power CO2 laser cutting were, for the first time, compiled in context and discussed regarding their impact on process quality. Above all the properties of the laser beam and process gas stream and the temperature distribution in the workpiece were experimentally investigated. A range of self designed and also commercially available diagnostic equipment was used on a conventional laser beam cutting machine. Simultaneously a technological investigation of laser beam cutting of metals was carried to detect the impact of the measurable variables on process quality. With that a basis was established for the future realization of online process diagnostics and closed-loop control system